Frequency Event Identification by a Lstm Network Approach - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2024)
The ongoing transition of electric grids has posed significant operational challenges for System Operators (SOs), which has led to the implementation of new data-based techniques and analysis. Various system operators and research projects have started to share different datasets, especially frequency data. This work proposes the development of a system based on LSTM networks for the detection of contingencies and the identification of characteristic patterns in frequency signals, while only storing relevant information. Therefore, it showcases a new tool that contains actual classified frequency events obtained from phasor measurement unit (PMU) recordings in the Chilean electric system. © 2024 IEEE.